Soluble serum interleukin 2 receptor levels in leprosy patients - Tung, K. S. K. (1987)
Soluble interleukin 2 receptors (IL-2R) in sera of leprosy patients from Chiang Mai, Thailand, were quantified with a solid phase enzyme immunoassay using two monoclonal antibodies to the IL-2R. The IL-2R levels of untreated lepromatous, borderline lepromatous or midborderline patients and treated lepromatous and borderline lepromatous or treated borderline tuberculoid and tuberculoid patients were comparable to those of the Thai household or nonhousehold contacts; and they were significantly higher than the levels of USA control subjects. In contrast, IL-2R of untreated tuberculoid or borderline tuberculoid patients were significantly reduced. Patients with ongoing reversal reaction had very high circulating IL-2R, the levels of which correlated with fever and extent of skin lesions. Although erythrema nodosum leprosum patients also had elevated IL-2R levels, they were significantly below those of patients with reversal reaction. When treated with corticosteroid, precipitous reduction of IL-2R was noted in all patients with reversal reaction but not in patients with erythema nodosum leprosum.